Political Parties as Legal Entities: An Academic Debate - Ghafur, Jamaludin; Sadzali, Ahmad; Rishan, Idul (KnE Social Sciences, 2023)
This paper aims to provide an academic brief on the status of political parties as legal entities amid debates on whether political parties stand as private or public legal entities. Based on doctrinal research, the results of the study conclude that although there is an impossibility to firmly place the position of political parties as public or private legal entities considering political parties do have two dimensions, namely private and public, the evidence shows that political parties are more appropriately positioned as legal entities under the public law based on three arguments. First, the party is an important and key institution for the success of democratic work. Second, the relationship between the party and the people is getting further apart, while the relationship between the political party and the state is getting stronger. Third, political parties receive the aid of public funding. Keywords: Political Party, Private, Public